PENGARUH KOMPETENSI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT FREEPORT INDONESIA - Teisly Monica Wuisan; Johny ., Kalangi; Wehelmina ., Rumawas (AGRI-SOSIOEKONOMI, 2021)
This study aims to determine how the influence of competence and job satisfaction affects the performance of PT Freeport Indonesia's employees. This research was conducted at PT Freeport Indonesia Kuala Kencana Office Building 2, Timika Regency. This research was conducted in January 2021. This research is a quantitative research with descriptive analysis. This study uses primary and secondary data. Primary data is the result of direct data collection from respondents by distributing questionnaires to 40 respondents who are employees of the Administration Division of PT Freeport Indonesia, Material Expediting, Bulk and Container. Secondary data is obtained from existing sources (PT Freeport employee evaluation reports, books, journals, websites and so on) for reference in making reports. Data analysis used SEM-PLS factor analysis. The results showed that competence and job satisfaction had a significant effect on the performance of PT Freeport Indonesia's employees.